Newspaper reporting on a cluster of suicides in the UK - John, A; Hawton, K; Gunnell, D; al., E (Hogrefe, 2016)
Background: Media reporting may influence suicide clusters through imitation or contagion. In 2008 there was extensive national and international newspaper coverage of a cluster of suicides in young people in the Bridgend area of South Wales, UK. Aims: To explore the quantity and quality of newspaper reporting during the identified cluster. Method: Searches were conducted for articles on suicide in Bridgend for 6 months before and after the defined cluster (June 26, 2007, to September 16, 2008). Frequency, quality (using the PRINTQUAL instrument), and sensationalism were examined. Results: In all, 577 newspaper articles were identified. One in seven articles included the suicide method in the headline, 47.3% referred to earlier suicides, and 44% used phrases that guidelines suggest should be avoided. Only 13% included sources of information or advice. Conclusion: A high level of poor-quality and sensationalist reporting was found during an ongoing suicide cluster at the very time when good-quality reporting could be considered important. A broad awareness of media guidelines and expansion and adherence to press codes of practice are required by journalists to ensure ethical reporting.